Metalanguage in the silent cinema (1896-1914): the seduction of the cinematographic apparatus, the paradoxes of the filmic image, the diegetic immersion (Significação: Journal of Audiovisual Culture, 2017)
The presence of metalanguage in the cinema is contemporary to the invention of the film device. The silent cinema has prodigally shown itself in function, with goals as vast as they are contradictory: to historicize aboutitself; to invite the audience to immerge in the filmic diegesis, while explaining the inherent discontinuity of the cinematic image; to wave to the paradoxes contained in the image, questioning its alleged “objectivity”. Through a transdisciplinary perspective this article aims to reflect upon the meanings of metalanguage in the cinema from 1896 to 1914.